2012
DOI: 10.5194/acpd-12-5487-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol-precipitation interactions in the southern Appalachian Mountains

Abstract: There are many uncertainties associated with aerosol-precipitation interactions, particularly in mountain regions where a variety of processes at different spatial scales influence precipitation patterns. Aerosol-precipitation linkages were examined in the southern Appalachian Mountains, guided by the following research questions: (1) how do aerosol properties observed during precipitation events vary by season (e.g., summer vs. winter) and synoptic event type (e.g., frontal vs. non-frontal); and (2) what infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Cluster analysis is a strong and essential technique known to be used to decipher the origin of air masses or the transport of pollutants arriving in a specific location. The HYSPLIT method is based on TSV (Lu et al 2018), representing the total variance between clusters, and on the other hand on SPVAR, which is the minimum increase of spatial variance between cluster components (Kelly et al 2012;Adame et al 2014;Stein et al 2015).…”
Section: Assessment Of Seasonal Changes Using Cluster Analysis Approachmentioning
confidence: 99%
“…Cluster analysis is a strong and essential technique known to be used to decipher the origin of air masses or the transport of pollutants arriving in a specific location. The HYSPLIT method is based on TSV (Lu et al 2018), representing the total variance between clusters, and on the other hand on SPVAR, which is the minimum increase of spatial variance between cluster components (Kelly et al 2012;Adame et al 2014;Stein et al 2015).…”
Section: Assessment Of Seasonal Changes Using Cluster Analysis Approachmentioning
confidence: 99%
“…The cluster technique implemented in the HYSPLIT model [22] was used to identify airflow patterns, and synoptic scenarios. This technique has worked very well in previous studies [23], and more information can be found in the HYSPLIT model user guide.…”
Section: Meteorological Parameters and Backward Trajectoriesmentioning
confidence: 82%
“…All of the back trajectories of each location were clustered using SPVAR (cluster spatial variance) calculations and then the total spatial variance (TSV) (Su et al 2015) was calculated, respectively. SPVAR is the sum of the squared distances between the endpoints of the cluster's component trajectories and the mean of the trajectories in that cluster (Draxler and Hess 1997;Perry and Soule 2012). Finally, the optimum number of clusters was selected using the TSV change as well.…”
Section: Source Identification Using Principal Component Analysismentioning
confidence: 99%